Congenital retinal macrovessel and the association of retinal venous malformations with venous malformations of the brain - Pichi, Francesco (2018)
Importance Congenital retinal macrovessel (CRM) is a rarely reported venous malformation of the retina that is associated with venous anomalies of the brain. Objective To study the multimodal imaging findings of a series of eyes with congenital retinal macrovessel and describe the systemic associations. Design, Setting, and Participants In this cross-sectional multicenter study, medical records were retrospectively reviewed from 7 different retina clinics worldwide over a 10-year period (2007-2017). Patients with CRM, defined as an abnormal, large, macular vessel with a vascular distribution above and below the horizontal raphe, were identified. Data were analyzed from December 2016 to August 2017. Main Outcomes and Measures Clinical information and multimodal retinal imaging findings were collected and studied. Pertinent systemic information, including brain magnetic resonance imaging findings, was also noted if available. Results Of the 49 included patients, 32 (65%) were female, and the mean (SD) age at onset was 44.0 (20.9) years. A total of 49 eyes from 49 patients were studied. Macrovessel was unilateral in all patients. Color fundus photography illustrated a large aberrant dilated and tortuous retinal vein in all patients. Early-phase frames of fluorescein angiography further confirmed the venous nature of the macrovessel in 40 of 40 eyes. Optical coherence tomography angiography, available in 17 eyes (35%), displayed microvascular capillary abnormalities around the CRM, which were more evident in the deep capillary plexus. Of the 49 patients with CRM, 39 (80%) did not illustrate any evidence of ophthalmic complications. Ten patients (20%) presented with retinal complications, typically an incidental association with CRM. Twelve patients (24%) were noted to have venous malformations of the brain with associated magnetic resonance imaging. Of these, location of the venous anomaly in the brain was ipsilateral to the CRM in 10 patients (83%) and contralateral in 2 patients (17%), mainly located in the frontal lobe in 9 patients (75%). Conclusions and Relevance Our study has identified an association between macrovessels in the retina and venous anomalies of the brain (24% compared with 0.2% to 6.0% in the normal population). Thus, we recommend new guidelines for the systemic workup of patients with CRM to include brain magnetic resonance imaging with contrast. These lesions may be more accurately referred to as retinal venous malformations, which may raise awareness regarding potential cerebral associations.